THE TRANSITION FROM MOTHER‐OF‐ONE TO MOTHER‐OF‐TWO: MOTHERS' PERCEPTIONS OF THEMSELVES AND THEIR RELATIONSHIPS WITH THEIR FIRSTBORN CHILDREN. Issue 4 (15th June 2017) - Chapman, Jennifer K.; Hart, Sybil L.
ABSTRACT: This qualitative study aimed to explore mothers' perceptions of the transition to second‐time motherhood, and advance methodology for supporting mothers during this transition. Fifty‐seven pregnant mothers and their firstborn children ( M age = 30.3 months) participated in a laboratory procedure in which the mother exposed her child to a brief episode of differential treatment. The episode was designed to simulate an expected experience of caregiving that would occur after the birth of a second child. During a postnatal visit ( M= 5.72 weeks following childbirth), mothers provided written feedback on their perceptions of the transition and the contribution of the laboratory experience to that transition. Qualitative content analysis revealed that mothers approached the birth of a second child with apprehension. Intrapersonal themes revealed that participation in the procedure shaped mothers' understanding of their expanded maternal roles by enhancing their sense of preparedness and confidence in their abilities to support their children. Interpersonal themes revealed that participation helped mothers appreciate the magnitude of the challenge that their children would face and gave mothers reason to believe that their children would adjust successfully. Findings are discussed in terms of their potential contribution toward developing methodology for helping mothers prepare for the addition of a second child.